Buckling performance of the encased functionally graded porous composite liner with polyhedral shapes reinforced by graphene platelets under external pressure. (February 2023) - Li, Zhaochao; Zhang, Qian; Shen, Hua; Xiao, Xinhui; Kuai, Haidong; Zheng, Junxing
Abstract: This paper aims to rehabilitate the deteriorated pipeline by using a novel thin-walled polyhedral liner with functionally graded porous (FGP) metal and graphene platelets (GPLs). The liner may buckle since the underground water flows into the damaged pipeline and hydrostatic pressure develops at the outer surface of the liner. Symmetrical distributions are applied to both the pores and the GPLs on the cross-section of the liner. A polyhedral profile is developed to improve flexural rigidity. By introducing radial displacement formulae and thin-walled shell theory, the expression of the potential energy is accomplished, by differentiating which, two equilibrium equations are expressed explicitly. Solving these two equations yields the critical buckling pressure. Subsequently, comparison studies are achieved when the polyhedral liner reduces to a conventional circular liner. The result indicates the present derivation is highly consistent with the other closed-form solutions for a circular liner. In addition, the buckling pressure may depend highly on some key parameters, such as the content of the pores, the GPLs, the polyhedral shapes, etc. These parameters are analyzed by parametric evaluations. Finally, an improvement factor is introduced to explore the effect of the polyhedral shapes on the buckling pressure of the encased thin-walled polyhedral FGP-GPLs liner. Highlights: A novel FGP-GPLs polyhedral liner is developed to restore the damaged pipeline. The FGP-GPLs polyhedral liner sustains much higher pressure than the circular one. Explicit equilibrium paths are obtained to describe the buckling mechanism.